The relative efficiency of commercial banks in Malaysia: (DEA) approach / Nurul Azwana Mohd Nordin - Mohd Nordin, Nurul Azwana (Bachelor Of Business Administration (Hons) Finance, 2012)
The study on efficiency of commercial banks is important for the Malaysian dual banking system where the Islamic banks are operating in parallel with the conventional banks. The relative efficiency of commercial banks using DEA Approach: Case of Local and Foreign Banks in Malaysia during the period of 2006-2010 are obtaining by using the non-parametric approach. This research therefore was conducted in objective to determine which commercial bank in Malaysia is efficient, to rank the commercial bank base on efficiency score and to recommend the solution to inefficient bank. The studies utilize CCR-model to measure the relative efficiency of the commercial banks. The study showed that there are 3 or 4 banks that efficient and another 8 or 9 banks were inefficient. These 3 banks that were efficient throughout the year 2006-2010 are Maybank, CIMB Bank and Standard Chartered Bank. Projection is used to improving these 9 inefficient Banks. The data were analyzed using Data Envelopment Analysis (DEA) system solver through the determinant of inputs and outputs for the DMUs. For this purpose, the researcher used secondary data, which is had been gather the data from Bank Scope and Data Stream and has focused to the commercial banks in Malaysia Thus, the finding from this study shows that by using DEA, it is easy to measure the relative efficiency of commercial banks in Malaysia.